Self-Cancellation of Interchannel Interference for OFDM Systems in Amplify-and-Forward Relay Communication Networks - Yu-Jun Won; Woo-Hyun Ahn; Jong-Won Choi; Bo-Seok Seo (International Journal of Distributed Sensor Networks)
We propose a method to compensate the effects of multiple carrier frequency offsets (CFOs) for orthogonal frequency division multiplexing (OFDM) systems. The multiple CFOs, we considered, are caused by several spatially separated frequency-unsynchronized transmitters as in amplify-and-forward relay communication networks or wireless ad hoc sensor networks. Despite its appealing features, OFDM is extremely sensitive to CFO, especially to multiple CFOs. At the receiver, the residual CFO which appears due to incomplete compensation of multiple CFOs destroys orthogonality among subcarriers and brings interchannel interference (ICI). In the proposed scheme, we compensate the CFOs of the received signal by the predesigned value, which results in cancellation of the opposite ICI by each other. This is based on the property that the spectrum of ICIs shown in a subcarrier has similar magnitudes and opposite signs from the fact that spectrum shapes of the ICI are of sinc function. Simulation results are shown to demonstrate the effectiveness of the proposed method.